Passive smoking: an environmental health risk - Bonneux, L G; Coebergh, J W (Nederlands tijdschrift voor geneeskunde, 2004)
The supposed health risks of passive smoking are leading to increasingly restrictive legislation on smoking. Tobacco smoke is undoubtedly irritating to the eyes, nose and throat of non-smokers, but politicians wanted more spectacular facts. There is some evidence of fatal consequences of passive smoking, particularly increases in lung cancer and heart-disease mortality among non-smokers exposed to tobacco smoke. Most studies compare the non-smoking partners of smokers and non-smokers. The observed relative risks are too small to be ascertained reliably. The more than twentyfold increased risk of lung cancer among smokers and the presence of tobacco-related metabolites in non-smokers' body fluids lend support to the hypothesis that passive smoking causes lung cancer. The less than twofold increased risk of heart disease among smokers and the documented social-risk factors cast doubt on the validity of the increased risk of heart disease in non-smokers, associated with having a smoking partner. The precautionary principle regulates potential environmental health hazards: the suspicion and the hazard must be sufficiently serious to take legislative action. There is ample evidence of tobacco smoke's carcinogenicity and the accumulated knowledge strongly suggests that the legal threshold of an acceptable environmental health risk has been exceeded.